Obstáculos à aceleração da taxa de crescimento equilibrado da economia brasileira: aspectos macroeconômicos e inserção nas Cadeias Globais de Valor - Helder Lara Ferreira Filho (2016)
The literature of demand-led growth models suggests that the long run sustainable growth rate of the economy can be restricted for Balance-of-Payments problems. This dissertation tries to demonstrate that this restriction can be relaxed with the conjunct development of a mature National Innovation System and the competitive ingression of a country in the so-called Global Value Chains. Through theoretical and empirical treatments during the dissertation, It is pointed that Brazil has not yet freed itself from the external restriction and neither has developed a mature Nation Innovation System or has ingressed in a qualified way to the Global Value Chains. More benign macroeconomic conditions, with the combination of a low and less volatile interest rate and a slightly undervalued and less volatile exchange rate, can favor this process.